Measurement principle and technology of miniaturized strapdown inertial wave sensor - Zhou, Fenghua; Zhang, Rongwang; Zhang, Shaowei (Frontiers in Marine Science, 2022)
This paper presents the design and implementation of a low-cost directional inertial wave sensor, DWS19-2, which is suitable for installation on ocean air-sea coupling buoys, offshore environmental monitoring buoys and surface drifting buoys. DWS19-2 integrates an STM32F446 embedded controller with a 9-axis MEMS inertial module QZ901 to measure buoy pitch, roll, heading and accelerations. These parameters are further used to calculate wave parameters and estimate directional and non-directional wave spectra. These wave parameters and spectral information are then reported to the buoy data logger for real-time transmission to shore-based data centers. Details of the electrical design and onboard wave processing algorithm (coordinate projection, numerical integration in the frequency domain, time-based wave parameters, frequency-based wave parameters, directional wave spectrum), in addition to turntable tests, filed marine comparison with DWR-MKIII wave buoy and related ocean observation applications enabled by this device, are described in this paper.